SKILLS AIMED AT DEVELOPING THE PROFESSIONAL COMPETENCE IN THE PROCESS OF TEACHER TRAINING - Yulduz Abdullayevna Djurayeva (Web of Journals Publishing, 2023)
This article analyzes professional competence, qualification requirements for modern specialists, effective use of methods and tools aimed at forming their professional competence in the process of training informatics and information technology teachers.
Keywords: Competence, professional competence, modern specialist, Insert method, traditional lesson, professional training, professional activity.